Prophylactic abdominal drainage following appendectomy for complicated appendicitis: A meta-analysis - Liao, Jiankun; Zhou, Jiansheng; Wang, Jialei; Xie, Guisheng; Wei, Haotang (Frontiers in Surgery, 2023)
Background This paper presents a meta-analysis of the effects of prophylactic AD on postoperative complications in patients with CA, with the goal of exploring the safety and effectiveness of prophylactic AD. Methods PubMed, Science Direct, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles published before August 1, 2022. Results The results of this meta-analysis showed that compared with patients in the non-drainage group, patients in the drainage group had longer postoperative length of hospitalization (LOH) (SMD = 0.68, 95%CI: 0.01 ~ 1.35, P= 0.046), higher overall incidence of postoperative complications (OR = 0.50, 95%CI: 0.19 ~ 0.81, P= 0.01), higher incidence of WI (OR = 0.30, 95%CI: 0.08 ~ 0.51, P= 0.01) and PI (OR = 1.05, 95%CI: 0.57 ~ 1.54, P= 0.01), the differences were statistically significant. The results of subgroup meta-analysis showed that in adult subgroup, the overall incidence of postoperative complications in drainage group was higher than that in non-drainage group (OR = 0.67, 95%CI: 0.37 ~ 0.96, P= 0.01). However, there were no significant differences in IAA (OR = 0.18, 95%CI: -0.28 ~ 0.64, P= 0.45) and WI (OR = 0.13, 95%CI: (-0.40 ~ 0.66, P= 0.63) and PI (OR = 2.71, 95%CI: -0.29 ~ 5.71, P= 0.08). In children subgroup, there were no significant differences in the incidence of IAA (OR = 0.51, 95%CI: -0.06 ~ 1.09, P= 0.08) between the two groups. The overall incidence of postoperative complications (OR = 0.46, 95%CI: 0.02 ~ 0.90, P= 0.04), incidences of WI (OR = 0.43, 95%CI: 0.14 ~ 0.71, P= 0.01) and PI (OR = 0.75, 95%CI: 0.10 ~ 1.39, P= 0.02) were significantly higher than those in the non-drainage group. Conclusions Although prophylactic AD does not benefit from appendectomy in adults with CA, it does not increase the incidence of major complications. Surgeons can use prophylactic AD according to the grade of appendicitis. However, prophylactic AD does not have the benefit of reducing postoperative complications in children with CA, but increases the incidence of postoperative complications. Meta-analysis results do not recommend prophylactic use of AD after complicated appendectomy in children.